Potential of Eco-enzyme Averrhoa bilimbi L. Fruit as an Innovation in Tempeh Wastewater Treatment in Plaju District, South Sumatra - Siti Soleha; Delima Engga Maretha; Andi Saputra (Journal of Multidisciplinary Applied Natural Science, 2025)
Tempeh home industries have been established in residential areas, one of which is in the assisted village of PT Pertamina Internasional RU III Plaju Factory, Palembang, South Sumatra. Eco-enzyme is one of the methods for processing and reducing pollutant organic matter in liquid waste. This study aims to determine the eco-enzyme characteristics of Averrhoa bilimbi L. fruit and exploit its potential to reduce chemical oxygen demand (COD), total suspended solid (TSS), and total dissolved solid (TDS) in tempeh wastewater. Eco-enzymes are characterized by measuring pH, COD, TSS, TDS, and most probable number (MPN). The reduction in COD, TSS and TDS of tempeh wastewater was observed using a simple bioreactor which was treated with the addition of 10% eco-enzyme (three replicates) and without the addition of eco-enzyme (control). The characterization results showed that the eco-enzyme of A. bilimbi L. fruit had a pH of 1.84, COD of 85.33 mg/L, TSS of 440 mg/L, TDS of 15,800 mg/L, protein concentration of 0.459 U/mg, and MPN value of 0.03 CFU/100 mL. The COD value of tempeh liquid waste can be reduced from the initial COD of 256 to 154.67 mg/L. The TSS value of tempeh wastewater decreased by 60% from the initial value of 4,000 mg/L. It takes 18 days to reduce the TSS content below the quality standard. The TDS value of tempeh liquid waste can be reduced by 70% from the initial TDS of 7,333.33 to 1,666.67 mg/L.